Relationship between Satisfaction and Academic Performance of Students at the College of Education - Ebenezer, Kwakwa; Adiyaa, Osei; Kumabia, Francis Koku Ras (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This study was a correlational research design. It was designed for investigating the  relationship between students’ satisfaction and academic performance among level  200 students of Mount. Mary College of Education in the Eastern Region of Ghana.  Purposive sampling technique was used to sample 200 students. Satisfaction of  Colleges of Education students were measured using adapted Student Satisfaction  Survey developed by Strachota (2006) on a 4 point Likert scale (from Not Satisfied  (1), Somehow Satisfied (2), Satisfied (3) and Highly Satisfied (4)) which has 8  items. Examination scores of four core subjects (Assessment in Basic Schools,  Curriculum Studies, English Language Studies II, Forms and Functions of English  Clause) in the first and second semesters of the 2020/2021 academic year were  used to measure students’ academic performance.
Keywords: Satisfaction; Academic performance; College of Education students